Experimental investigation on solid particle erosion behaviour of glass/epoxy Quasi-isotropic laminates. (12th June 2019) - Padmaraj, N H; Vijaya, Kini M; Dayananda, Pai
Abstract: The erosion behaviour of glass/epoxy quasi-isotropic laminates were investigated using Aluminium Oxide as erodent. Mass loss of the target material was used to estimate the erosion rate. An erosion rate prediction model was developed using Response Surface Methodology by considering impact angle, impact velocity and feed rate as the input variables. Analysis of variance of the results predict that impact angle and velocity were the major independent parameters influencing the erosion rate. Higher impact angle and lower feed rate exhibited high erosion rate; lower velocity and high feed rate resulted in lower erosion rate. Surface morphology of the specimens with low and high erosion resistance were studied using scanning electron microscopic technique.